Sliding Mode based Circle Search Algorithm for Inventory Control with Extended State Observer - Neamah D. Farhan; Raya K. Naji; Muntaha K. Musa; Huda A. Kanber; Wafaa H. Abdul Hadi; Aws M. Abdullah; Hussien Dulaimi; Huthaifa Al-Khazraji (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
The efficient utilization of inventory systems has become increasingly important in modern industrial practice due to its substantial contribution to cost reduction, resource optimization, and overall operational efficiency. Sliding mode control (SMC) is presented in this study for management and optimization of the inventory systems. First, the differential equations of inventory system are developed. Then, the SMC is employed for the improvement of the performance of the inventory system under time varying demands, by minimizing tracking error and improving reference following. Moreover, an extended state observer (ESO) is introduced to compensate for the lack of direct access to the system state variables by estimating the unavailable states while simultaneously providing demand estimation. Furthermore, circle search algorithm (CSA) is used for optimizing the SMC and the ESO because of its outstanding global optimization potential and to provide a good balance between exploitation of the obtained solutions and exploration of new ones during the search process by means of the integral of absolute error (IAE). The efficacy of the ESO to estimate the states of the system and the profile of the unknown demand has been validated by computer simulation in the MATLAB. Additionally, The proposed ESO-SMC is examined with the proportional, integral, derivative (PID) controller of the stochastic demand. This test shows the ESO-SMC to be superior in their performance enhancement, especially the reduction of inventory costs.